Nursing with heart: Analyzing the influence of motivation and remuneration in improving nurse performance at RSJ Mutiara Sukma - Hidayati, Fitria; Saimi, Saimi (Institute of Computer Science (IOCS), 2024)
The role of nurses in Mental Health Hospitals (RSJ) is crucial in providing quality mental health care. Motivation and remuneration have been identified as key factors influencing nurse performance in RSJs. This study aims to explore the influence of motivation and remuneration on nurse performance at RSJ Mutiara Sukma. A qualitative approach with regression analysis was used in this study. A sample of 110 nurses was randomly selected from the total population of 153 nurses at RSJ Mutiara Sukma. Data were collected through in-depth interviews and observations. The analysis results showed a significant relationship between motivation, remuneration, and nurse performance. High motivation, both intrinsic and extrinsic factors, positively contributed to nurse performance. Similarly, fair and adequate remuneration also influenced the improvement of nurse performance. These findings emphasize the importance of considering motivation and remuneration as key factors in enhancing nurse performance at RSJ Mutiara Sukma. Hospital management should consider implementing policies that support intrinsic and extrinsic motivation and ensure a fair remuneration system as strategies to improve the effectiveness of mental health care services in the institution.